Comprehensive Analysis of the Genetic and Epigenetic Mechanisms of Osteoporosis and Bone Mineral Density - Dong, Hui; Zhou, Wenyang; Wang, Pingping; Zuo, Enjun; Ying, Xiaoxia; Chai, Songling; Fei, Tao; Jin, Laidi; Chen, Chen; Ma, Guowu; Liu, Huiying (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis is a skeletal disorder characterized by a systemic impairment of bone mineral density (BMD). Genome-wide association studies (GWAS) have identified hundreds of susceptibility loci for osteoporosis and BMD. However, the vast majority of susceptibility loci of osteoporosis are located in non-coding regions of the genome and provide limited information about the genetic mechanisms of osteoporosis. Herein we performed a comprehensive analysis of genetic and epigenetic mechanisms osteoporosis and BMD, and obtain new insights into the osteoporosis. BMD and osteoporosis were found to share many common susceptibility loci, and the corresponding susceptibility genes are significantly enriched in bone-related biological pathways. The regulatory element enrichment analysis indicated that BMD and osteoporosis susceptibility loci are significantly enriched in 5’UTR and DNase I hypersensitive sites in peripheral blood immune cells. By integrating GWAS and expression Quantitative Trait Locus (eQTL) data, we found that 15 protein-coding genes are regulated by the osteoporosis and BMD susceptibility loci. Our analysis provides new clues for a better understanding of the pathogenic mechanisms and potential therapeutic targets for osteoporosis.